Optimizing academic library services in the digital milieu : digital devices and their emerging trends - Ryan, Brendan (Chandos information professional series, 2013)
Optimizing Academic Library Services in the Digital Milieu identifies best practices and strategies for using digital devices (such as tablets, e-readers, and smartphones) and copyrighted materials in academic libraries